Case report: Lympho-histiocytic meningoencephalitis with central nervous system vasculitis of unknown origin in three dogs - Zdora, Isabel; Raue, Jonathan; Söbbeler, Franz; Tipold, Andrea; Baumgärtner, Wolfgang; Nessler, Jasmin Nicole (Frontiers in Veterinary Science, 2022)
Meningoencephalitis of unknown origin (MUO) is an umbrella term for a variety of subtypes of meningoencephalitis of dogs and cats with no identifiable infectious agent. In dogs, granulomatous meningoencephalitis (GME), necrotizing meningoencephalitis (NME), and necrotizing leukoencephalitis (NLE) are the most commonly reported subtypes. However, sporadically there are reports about other subtypes such as greyhound encephalitis or eosinophilic meningoencephalitis. The following case series presents three dogs with peracute to acute progressive signs of encephalopathy. The magnetic resonance imaging (MRI) of two dogs (post mortem n=1/2) showed severe, diffuse swelling of the cortical grey matter with increased signal intensity in T2weighted (w) and fluid-attenuated inversion recovery (FLAIR) and decreased signal intensity in T1w. Additionally, focal to multifocal areas with signal void in both dogs and caudal transforaminal herniation of the cerebellum in one dog was observed. Post mortem histopathological examination revealed lympho-histiocytic encephalitis and central nervous system (CNS) vasculitis in all dogs. No infectious agents were detectable by histopathology (hematoxylin and eosin stain), periodic acid-Schiff reaction (PAS), Ziehl-Neelsen stain and immunohistochemistry for Canine adenovirus-1, Parvovirus, Listeria monocytogenes, Parainfluenzavirus, Toxoplasma gondii, Herpes-suis virus, Pan-Morbillivirus, Tick born encephalitis virus, Severe acute respiratory syndrome coronavirus (SARS-CoV) 2. Furthermore, two dogs were tested negative for rabies virus. To the best of the authors’ knowledge, this is the first report of a lympho-histiocytic encephalitis with CNS vasculitis with no identifiable infectious agent. It is suggested to consider this as an additional subtype of MUO with severe clinical signs.